Herbert Spencer correspondence - Spencer, Herbert, 1820-1903.
Four ALS from Spencer, including two letters of introduction (1868 February 29 and 1869 January 15) for Nicholas Leon Thieblin, a letter (1868 June 25) written by him to Thieblin, and a letter (1867 December 30) to an unknown recipient regarding a translation of his book, First Principles of a New System of Philosophy (1864).
Philosopher.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Spencer, Herbert, -- 1820-1903. -- Translations; Thieblin, Nicholas Leon, -- 1834-1889.; Philosophers